Cover Image, Volume 14, Issue 3. (2nd August 2016) - Scarpa, Filippo; Sabattini, Silvia; Bettini, Giuliano
Abstract : The cover image, by Giuliano Bettini et al., is based on the Original Article Cytological grading of canine cutaneous mast cell tumours, DOI:10.1111/vco.12090 . Abstract : The cover image, by Giuliano Bettini et al., is based on the Original Article Cytological grading of canine cutaneous mast cell tumours, DOI:10.1111/vco.12090 .